2010
DOI: 10.1016/j.bpj.2010.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Material Properties of Lipid Microdomains: Force-Volume Imaging Study of the Effect of Cholesterol on Lipid Microdomain Rigidity

Abstract: The effect of cholesterol (CHOL) on the material properties of supported lipid bilayers composed of lipid mixtures that mimic the composition of lipid microdomains was studied by force-volume (FV) imaging under near-physiological conditions. These studies were carried out with lipid mixtures of dioleoylphosphatidylcholine, dioleoylphosphatidylserine, and sphingomyelin. FV imaging enabled simultaneous topology and force measurements of sphingomyelin-rich domains (higher domain (HD)) and phospholipid-rich domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 82 publications
4
25
0
Order By: Relevance
“…NAbs exclusively interacted with the lipid phase with the lowest height and therefore the lowest lipid packing density, the largest membrane disorder, and the highest lipid diffusivity. (2325) This result is in agreement with a previous AFM study completed by Franquelim et al(18) The lipid diffusivity in the L o phase is approximately a factor 2–10 smaller than in the L d phase, depending on experimental details. (2628) The presence of cholesterol is a major contributor to the physical properties of lipid domains.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…NAbs exclusively interacted with the lipid phase with the lowest height and therefore the lowest lipid packing density, the largest membrane disorder, and the highest lipid diffusivity. (2325) This result is in agreement with a previous AFM study completed by Franquelim et al(18) The lipid diffusivity in the L o phase is approximately a factor 2–10 smaller than in the L d phase, depending on experimental details. (2628) The presence of cholesterol is a major contributor to the physical properties of lipid domains.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that the force required to break the intermolecular lipid interactions in a cholesterol-rich L o phase is greater compared to that in a cholesterol-depleted L d phase. (25) This supports the hypothesis that the high order of L o and gel domains prevented NAb insertion into these SLB areas.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, it has been shown conclusively that the net charge of liposomes and the firmness of the membranes determine the effect on hemostasis. 4,32,36 Although the antihemostatic activity observed in our experiments with FBN-coated liposomes cannot be ascribed to the γ ′ chain of FBN, our results (reduced thrombin generation, inhibition of ristocetin-induced aggregation, decrease in fibrin density and inhibition of thrombus formation) show behavior similar to that described for the γ ′ chain. 11,37 This could be explained by a global negative charge in our liposomes 17 and the use of thiolated FBN during the binding procedure, which could induce residue sulfation and generate conformational changes in the molecule similar to those observed in the γ ′ chain.…”
Section: Discussionsupporting
confidence: 75%
“…During the last five years, high resolution Force Volume has been employed to investigate biological systems, including proteins in their native conditions (Alsteens et al ., ; Pfreundschuh et al ., ) or phase separating SLBs (An et al ., ; Sullan et al ., ; Li et al ., ; Picas et al ., ). At the present time, many commercial AFM systems provide data processing tools which allow the extraction of conventional information associated to force–distance curves, such as adhesion force or sample elasticity.…”
Section: Introductionmentioning
confidence: 99%